Physiological changes in the locomotor system of a pregnant and related lumbar-sacral pain - examination of the degree of feeling back pain during properly running pregnancy - Katarzyna Urtnowska; Irena Bułatowicz; Agnieszka Radzimińska; Magdalena Woźniak; Jacek Wiśniewski; Walery Zukow (Kazimierz Wielki University, 2015)
Urtnowska Katarzyna, Bułatowicz Irena, Radzimińska Agnieszka, Woźniak Magdalena, Wiśniewski Jacek, Zukow Walery. Fizjologiczne zmiany w układzie ruchu ciężarnej oraz związane z tym dolegliwości bólowe odcinka lędźwiowo - krzyżowego - badanie stopnia odczuwania bólu kręgosłupa w trakcie prawidłowo przebiegającej ciąży = Physiological changes in the locomotor system of a pregnant and related lumbar-sacral pain - examination of the degree of feeling back pain during properly running pregnancy. Journal of Education, Health and Sport. 2015;5(7):105-116. ISSN 2391-8306. DOI 10.5281/zenodo.19324 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A96-104 https://pbn.nauka.gov.pl/works/578814 http://dx.doi.org/10.5281/zenodo.19324 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 30.06.2015.   Fizjologiczne zmiany w układzie ruchu ciężarnej oraz związane z tym dolegliwości bólowe odcinka lędźwiowo - krzyżowego - badanie stopnia odczuwania bólu kręgosłupa w trakcie prawidłowo przebiegającej ciąży Physiological changes in the locomotor system of a pregnant and related lumbar-sacral pain - examination of the degree of feeling back pain during properly running pregnancy   Katarzyna Urtnowska, Irena Bułatowicz1, Agnieszka Radzimińska1, Magdalena Woźniak2, Jacek Wiśniewski2, Walery Zukow3   1. Katedra Fizjoterapii Zakład Kinezyterapii i Masażu Leczniczego Collegium Medicum Uniwersytet Mikołaja Kopernika w Toruniu 2. Katedra Kosmetologii i Dermatologii Estetycznej Collegium Medicum Uniwersytet Mikołaja Kopernika w Toruniu 3. Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy   Część I: Zmiany w układzie ruchu Part I: Changes in the locomotor system   Słowa kluczowe: ciąża, układ ruchu, ból pleców.   Streszczenie W trakcie ciąży w organizmie kobiety dochodzi do szeregu modyfikacji mających na celu zapewnienie miejscowych warunków do rozwoju i wzrastania płodu. Dzięki funkcji, początkowo ciałka żółtego, a następnie łożyska oraz szeregom zjawisk hormonalnych dochodzi do przekształceń w całym organizmie. Celem rozwoju płodu ciało kobiety musi ulec między innymi wielu mechanicznym zmianom adaptacyjnym, które obejmują układ ruchu: mięśniowo - więzadłowy i kostno - stawowy.           W prawidłowo przebiegającej ciąży to właśnie one są najbardziej zauważalne i mimo,                           iż całkowicie prawidłowe, często dają objawy bólowe.   Key words: pregnancy, musculo-skeletal system, low-back pain.   Summary During pregnancy a woman's body passes through a series of anatomical changes, whose purpose is  to ensure local conditions for the development and growth of the fetus. A number of modifications throughout the whole woman organism occurs thanks to initially corpus luteum, and then placenta, and a series of hormonal transitions. As to provide proper conditions for the development of the fetus, a woman's body must go through a number of mechanical adaptive changes, which includes the changes of the motor system: ligament - muscular system and bone - joint system. In a properly running pregnancy this adjustments are the most noticeable and although completely correct, often produces symptoms of pain.   Część II: Dolegliwości bólowe odcinka lędźwiowo - krzyżowego kręgosłupa w trakcie ciąży   Part II: Aches and pains lumbar-sacral spine during pregnancy   Słowa kluczowe: ciąża, układ ruchu, ból pleców.   Streszczenie Wprowadzenie: Dolegliwości bólowe odcinka lędźwiowo - krzyżowego kręgosłupa, są bardzo istotnym problemem medycznym i występują u 45 - 56% kobiet w ciąży. Główną przyczyną bólu pleców u ciężarnych są dysfunkcje stawowe, więzadłowe i mięśniowo-powięziowe, powstałe na skutek zmiany statyki ciała spowodowanej nagłym i dużym przyrostem masy ciała zlokalizowanym w okolicy brzucha. Cel badania: Celem badania było wykazanie czy i w jakim stopniu u kobiet w ciąży występują dolegliwości bólowe odcinka lędźwiowo - krzyżowego kręgosłupa, oraz określenie czy istnieje zależność pomiędzy stopniem ich odczuwania, a wiekiem ciężarnej, zaawansowaniem ciąży i kolejnymi ciążami. Metody i materiały: W sondażu diagnostycznym udział wzięło 180 kobiet będących w ciąży, które udzieliły odpowiedzi na 30 pytań. Wyniki: Zdecydowana większość ciężarnych w mniejszym, lub większym stopniu odczuwała dolegliwości bólowe odcinka lędźwiowo - krzyżowego kręgosłupa. Odczuwalność bólu pleców wzrastała wraz ze stopniem zaawansowania ciąży, a dodatkowo stwierdzono, iż częściej doświadczały go młodsze panie niż starsze. Wnioski: Uzyskane wyniki potwierdzają, iż dolegliwości bólowe odcinka lędźwiowo - krzyżowego kręgosłupa są bardzo częstym problemem kobiet w ciąży   Key words: pregnancy, musculo-skeletal system, low-back pain.   Summary Indroduction: Lower back pain is a very important medical problem and occur in 45 - 56%               of pregnant women. The main cause of pregnancy back pain are dysfunctions of joints, muscle and ligaments, resulting from changes in the posture, which is caused by a sudden and large increase of the body mass located mostly in the abdomen. Objective: The aim of the study was to determine whether and to what extent, pregnant women are suffering from low back pain, and to determine whether there is a correlation between the degree of the pain, and the age of the pregnant woman, pregnancy progresses and a number of pregnancies before. Materials and methods: A number of 180 pregnant women participated in a survey and responded to a number of 30 questions. Results: The vast majority of pregnant women more or less suffered from low back pain. Sensibility of back pain increased with the progress of the pregnancy, and additionally younger women experienced it more often than older ones. Conclusions: The results confirm that the lower back pain is a very common problem for women during pregnancy.